Specific Methanogenic Activity: Simplified and automated methodologies for sludge of anaerobic reactors - Cordeiro, Ana Luiza; Móller, Débora Salomé; Dutra, Joyce da Cruz Ferraz; Carvalho, Ana Teresa Silva de; Souza, Cláudio Leite de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2018)
The test of specific methanogenic activity (SMA) allows knowledge about the potential of anaerobic sludge in the digestion of organic material, however, it does not yet have a practical protocol for its most widespread development in the Treatment Stations. The present work intends to make a comparison between two SMA methods, one simplified and one automated. In both methods there was inoculation of anaerobic reactor sludge, dilution with nutrient solution and addition of substrate (sodium acetate), in adequate concentrations. For the simplified method, antibiotic flasks were used with manual measurement of biogas production using a glass syringe and methane analysis via chromatography. In the automated method, the AMPTS (Automatic Methane Potential Test System) was used, which provided the results through interface with specific software. The results obtained with the simplified method were more coherent than expected (values around the range of 0.2 to 0.3 gDQOCH4/gSV.d), reliable and of lower cost, considering all the material resources involved, when compared with the obtained with automated method (values around 0.1 gDQOCH4/gSV.d). In addition, it has been found that new practices can be implemented.